Literature of the Golden Horde in the context of historical and cultural discourse - Khamraev Әлімжан (Turkic Studies Journal, 2024)
The literature of the Golden Horde era was the most important source of ideology for the consolidation of the state system. There was a growing need to portray socio-cultural problems related to the times and needs of a vast empire. This was essential to prevent endless conflicts between different social and ethnic groups that could undermine the foundations of society. Objectively, it was argued, it was expedient to establish moral principles to strengthen the foundations of Empire. Such a mission was entrusted to verbal art, which had a considerable impact on state foundations. The scientific world has received information about the functioning of religion and the degree of development of the spiritual culture of the Golden Horde thanks to the works of Mukhabaratname «Revandi Khorezmi»,»Qisas st anbiye» Rabguzi,»Khosrow and Shirin» by Qutb,»Gulistan bit-Turki» and «Suheil and Guldersen» by Saif Sarai, «Jumjuma Sultan» by Husama Katib and others. The need to establish a single government and uniform laws over a vast territory arose from the diversity of races, languages, socio-cultural and religious beliefs. In the era of the formation of the Golden Horde, religious and cultural leaders could clearly and rationally explain the origin of the concept of the «Ilakh».